PEMBERDAYAAN ANAK-ANAK PEKERJA MIGRAN INDONESIA DI MALAYSIA MELALUI PENDIDIKAN NONFORMAL DI SANGGAR BIMBINGAN KEPONG - Rachmawati, Andini; Alde Mulia Putra; Eka Indah Nuraini; Azra Nawal Aulia; Rina Noer Afifah; Roshida Yulia Rindang; Rifdah Syifa Rabbani (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Children of Indonesian Migrant Workers face various challenges, especially limited access to formal education, which impacts the development of their social and leadership skills. This service activity aims to increase children's courage, communication skills, and leadership through speech and ceremony training per the 1945 Constitution. The method used is non-formal education with a workshop approach and hands-on practice with around 30 migrant worker children. The training is held every Friday with a rotating system, allowing children to practice public speaking and expressing opinions. Evaluation was conducted through observation, interviews, and documentation of activities. The results showed significant improvements in public speaking confidence, organization of ideas, and interpersonal communication skills. This activity is effective in helping to develop the soft skills of children of migrant workers. For sustainability, increasing volunteers, collaborating with the government and NGOs, and developing a more structured non-formal education model is recommended.